Methylnaltrexone use in patient with opiod induced constipation – case report - Dzierżanowski, Tomasz (Medycyna Paliatywna/Palliative Medicine, 2009)
Constipation in palliative care patients has multifactor aetiology. In this case report, the author raises the problem of constipation appearing in an opioid-treated patient in spite of prophylactic means applied. Subcutaneous methylnaltrexone was used, but the first dose proved unsuccessful. Regular bowel movements started after the second dose. Attention has been drawn to difficulties in the treatment of opioid-induced constipation, when in some cases the use of more than one dose of methylnaltrexone may prove necessary to reverse a constipating effect of opioids and maintain effective bowel movements.